Potent Tumor-Specific Protection Ignited by Adoptively Transferred CD4(+) T Cells - Liu, Zuqiang (2008)
Administration of α-CD25 mAb prior to an aggressive murine breast tumor inoculation provoked effective antitumor immunity. Compared to CD4(+) T cells purified from α-CD25 mAb-pretreated mice that did not reject tumor, CD4(+) T cells purified from α-CD25 mAb-pretreated mice that rejected tumor stimulated by DCs produced more IFN-γ, IL-2 and less IL-17 in vitro, and ignited protective antitumor immunity in vivo in an adoptive transfer model. Tumor Ag-loaded DCs activated naïve CD8(+) T cells in the presence of these CD4(+) T cells in vitro. Tumor Ag and adoptively transferred CD4(+) T cells were both required for inducing a long-term tumor-specific IFN-γ-producing cellular response and potent protective antitumor activity. While adoptively transferred CD4(+) T cells ignited effective tumor-specific antitumor immunity in wild type mice, they failed to do so in endogenous NK cell-depleted, Gr-1(+) cell-depleted, CD40(-/-), CD11c(+) DC-depleted, B cell(-/-), CD8(+) T cell-depleted or IFN-γ(-/-) mice. Collectively, the data suggests that adoptively transferred CD4(+) T cells orchestrate both endogenous innate and adaptive immunity in order to generate effective tumor-specific long-term protective antitumor immunity. The data also demonstrates the pivotal role of endogenous DCs in the tumor-specific protection ignited by adoptively transferred CD4(+) T cells. Thus, these findings highlight the importance of adoptively transferred CD4(+) T cells, as well as host immune components, in generating effective tumor-specific long-term antitumor activity.